Treatment of Chronic Periodontal Disorders: A General Practitioners Perspective - Ayesh Das1 , Gatha Mohanty2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
A greater number of patients will experience gums-associated disorders at one or the other point in theirlifetime and also a section of the community is suspected to suffer from advanced gum associated disorders.Sound treatment is essential in dental practice (i.e. dental practitioner’s perspective). A comprehensivelayout of treatment which includes gum assessment, treatment, revisit of long-standing periodontitis casesin regular dental care, and treatment is discussed in this review.